ISIS Ex-WNI or Indonesian Ex-ISIS? An Overview in the Perspective of National Law and International Law - Eka Widi Astuti; Xavier Nugraha (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In Indonesia, there is a debate regarding the repatriation of former ISIS citizens. One of the main issues is related to the legal protection that will be provided by the state to them, especially their citizenship status. Based on this background, the formulation of the problem in this article is legal protection for Indonesian Ex- ISIS. This article uses a legal research method with a statutory and conceptual approach. Based on the results, it was found that several Indonesian laws and regulations and several international legal instruments expressly recognize the existence of citizenship as a fundamental right for everyone, and no one can arbitrarily revoke or be denied the right to change their citizenship. Sanctions for revocation of one's citizenship status cannot be applied equally to someone whose involvement is only limited to believing in theories, doctrines, or understanding terrorism under the guise of a certain religion. Elimination of citizenship rights by a country is an act that is not taken for granted. The decision-making on the Indonesian Ex- ISIS must still refer to the principle of protecting Human Rights (HAM) and several other international legal instruments.